Manajemen Kepemimpinan Kepala Sekolah Dalam Mewujudkan Sekolah Adiwiyata - Qowiyul Amin; Romi Siswanto (THE JOER: Journal Of Education Research, 2023)
This research was taken place in SDN Genukwatu 1 which aims to determine the leadership management function of the Principal at SDN Genukwatu 1 and the principal's efforts in realizing the Adiwiyata school. The study used qualitative methods with data collection techniques of participation observation, interviews, and documentation. Sources of data in this study were the principal, Adiwiyata Team, and students. To check the validity of the data, researchers used triangulation. The results of this study indicate, 1) The principal implements four management functions in implementing the Adiwiyata program. It is proven in the field that principals carry out management functions starting from planning (Developing vision, mission, goals, curriculum documents, and middle-term school programs), organizing (compiling the Adiwiyata team), implementing, and controlling (monitoring and evaluating) the programs being run, 2) The principal takes managerial steps and implements strategies to realize the Adiwiyata school. Principals also develop policies to support the implementation of the school's Adiwiyata program.